New species of Caprella (Crustacea: Amphipoda) from the Gulf of Oman, Iran - Momtazi, Farzaneh; Sari, Alireza; Darvish, Jamshid (Zootaxa, 2020)
Caprella moradi sp. nov. is described from intertidal zone of the Gulf of Oman, Iran. This species is differentiated from the most similar species Caprella danilevskii (Czerniavski, 1868), by four rows of fine setae on the body surface and bears a curved anterior surface of propodus in the second male gnathopod.